Pemagangan di Rumah Sakit Pertamedika Ummi Rosnati Kota Banda Aceh - Reza Kurnia; Ahul Ikbar; Intan Suci Arazaika; Irrazatul Azmi; Ilfa Safahanur; Alisa Rahayu; Fiska Amelia; Kurniati; Muhammad Haikal; Nada Nur Kamaria; Asmuri Yadna (Indonesia Berdampak: Jurnal Pengabdian kepada Masyarakat, 2025)
Internship students were placed at Pertamedika Ummi Rosnati Hospital in Banda Aceh for four weeks, allowing them to learn and gain practical experience in the hospital's activities. Observations revealed that Pertamedika Ummi Rosnati Hospital (RSPUR) in Banda Aceh was established as a private hospital focused on high-quality healthcare with an Islamic touch.